Reasons for non-response to a direct-mailed FIT kit program: lessons learned from a pragmatic colorectal-cancer screening study in a federally sponsored health center - Coronado, Gloria D (Transl Behav Med, 2014)
Colorectal cancer screening rates are below optimal. As part of a pilot clinic-based pragmatic study aiming to raise rates of colorectal-cancer screening, we explored patients’ reasons for not responding to a direct-mailed screening invitation. We conducted telephone interviews with patients who were mailed a fecal immunochemical test (FIT) but who did not return it to the lab. Interviews were audio-recorded, transcribed, and coded for thematic analysis. We met our goal of 20 interviews (10 in English and 10 Spanish; 75 % female). Reasons for not completing tests were fear of results or cost of follow-up colonoscopy (n = 9); not having received the test in the mail (n = 7); concerns about mailing fecal matter or that test results could be mixed up (n = 6); and being busy or forgetful (n = 4). Efforts to improve uptake of colorectal cancer screening in a direct-mailed program ought to address concerns identified in our study. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13142-014-0276-x) contains supplementary material, which is available to authorized users.